ՀՀ-ՆԱՏՕ փոխգործակցության ազդեցությունը պաշտպանական բարեփոխումների վրա (2005-2015 թթ.) - Գոռ Թովմասյան (ՀՀ ԳԱԱ հրատ.)
В статье анализируются основные результаты партнерства Армении с НАТО с начала декабря 2005 г. Особое внимание уделяется ключевым событиям, имевшим место после вступления в силу Индивидуального плана партнёрства с НАТО в 2005 г. до Второго стратегического пересмотра обороны РА.The article analyzes the major outcomes of Armenia-NATO partnership initiated in early December 2005. Special attention is paid to the key events that had taken place between the year 2005, when the Individual Partnership Action Plan came into force, and the second Strategic Defence Review in 2015.
Keywords: Political Science